Contemporary changes and civil society in Portugal and the Russian Federation*. Issue 3 (27th May 2019) - Casanova, José Luís; Guerreiro, Maria das Dores; Pervova, Irina
ABSTRACT: Portugal and the Russian Federation share some aspects of traditional culture and similar experiences in modern history, but they also exhibit significant differences that determine specific modes of civil society's development. Results of a comparative and diachronic analysis show that the major differences between the two countries reside in civil society's openness and composition. Organized civil society is not very distinct in relative size when comparing Portugal and the Russian Federation, but it is globally more autonomous, expressive, trusted and institutionalized in Portugal than in the Russian Federation and among the factors that contribute to this condition are an earlier and revolutionary transition to democracy, a larger middle class, a greater prevalence of the value of interdependence, and a regime that endorses bigger public social expenditure in Portugal, all this within the framework of the European Union that has a longer history of social demand and institutional incentives for civil society. Despite those unequal conditions, civil society faces similar current challenges in both countries, mainly with the outsourcing of the public provision of social services.